JAU-21: A NOVEL HIGH YIELDING AND DISEASE RESISTANT SIX-ROWED BARLEY VARIETY FOR RAINFED AND IRRIGATED AREAS OF PUNJAB, PAKISTAN - AHMAD, J; AJMAL, S; ZULKIFFAL, M; AHSAN, A; ABDULLAH, .; RAMZAN, Y; SARWAR, M; SHAMIM, S; MEHMOOD, A; ASGHAR, S; RIAZ, M (Biological and Clinical Sciences Research Journal, 2024)
The rise of sustainable barley production dictates the development of new barley varieties with enhanced yield and resistance to biotic and abiotic stresses. WRI, AARI, Faisalabad, Pakistan has released several barley varieties together with JAU-21 since its formation. Jau-21 is a six-row barley variety that can grow and ripen in a shorter time was selected from the international nursery GSBSN received from the International Center for Agriculture Research and Dry-land Area, Egypt during 2014-15. The revealed genotype with variety code B-15018 was further appraised in preliminary and regular during 2015-17 which super seated 21.65% than Haider-93 check on average bases. In the Punjab uniform barley yield trial, the proposed line outclassed the same check varieties by 20.29% over different settings of Punjab in 2017-18. It was further tested for yield and disease constancy in the national uniform barley yield trial, it excelled at 10.31 and 4.46 % over Haider-93 and Sultan-17, respectively during 2018-19 and 14.66 and 9.93% over Jau-87 and Jau-17, respectively in 2019-20 %. It can tolerate rust by displaying disease reactions from 0 to traces rather than 100 MS over check. Agronomic judgments and quantitative and qualitative analyses were also performed during 2017-18 to 2019-20. Due to its bold grain, auspicious yield performance, and appealing rust resistance trait over multi-location, the Punjab Seed Council approved B-15018 in 2021 with the name “Jau-21” for general cultivation in irrigated and rainfed areas of Punjab, Pakistan.